Electrical stimulation: a missing key to promote maturation of human pluripotent stem cell-derived cardiomyocytes in three-dimensional cardiac tissues - Sterckel, Sem; Passier, Robert; Rivera-Arbelaez, José Manuel (Frontiers in Bioengineering and Biotechnology, 2025)
The maturation of human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) remains a major challenge in developing functional in vitro cardiac models. While three-dimensional (3D) culture systems improve structural and metabolic properties, they do not fully recapitulate adult cardiomyocyte physiology. Exogenous electrical stimulation has emerged as complementary strategy to further drive maturation. This review highlights both the maturation effects of electrical pacing in 3D cardiac tissues, including enhanced sarcomere organization, conduction velocity, calcium handling, and contractile function. It also discusses the technological parameters used to achieve these outcomes, such as electric field voltage (EFV), pulse duration (PD), stimulation waveform, electrode materials, and pacing protocols, and how these factors influence hPSC-CM development. Despite progress, further research is needed to optimize stimulation setups and to integrate electrical pacing with other maturation cues. Advancing high-throughput, miniaturized platforms will be essential for translating these models into biomedical applications like drug discovery and disease modeling.